Upaya Guru dalam Meningkatkan Kedisiplinan Shalat Berjamaah pada Murid Kelas V Madrasah Ibtidaiyah Al-Hikmah - Kaif, Sitti Hermayanti; Fajrianti, Fajrianti; Haswan, Haswan; Satar, Iqram; Haliza, Siti Nur (EDUPEDIA Publisher, 2025)
Prayer serves as a fortress to protect humans, especially Muslims, from vile and sinful acts. Congregational prayer is a prayer performed together by at least two or more people with an imam and a congregation. There are many benefits of congregational prayer, including gaining rewards twenty-seven degrees compared to praying alone. Congregational prayer can protect a Muslim from neglecting, neglecting, or forgetting prayer and prevent him from praying at the end of the prayer time. The law of congregational prayer is Sunnah muakad which is a Sunnah that is highly recommended for Muslims, and some scholars say that the law of congregational prayer is fardhu kifayah. This PKM activity aims as an effort by teachers to improve discipline in congregational prayer among fifth grade students of Madrasah Ibtidaiyah Al-Hikmah. Activities carried out starting from socialization activities, implementation of teaching materials (practical prayer procedures), and evaluation. The implementation of the activity has a positive impact on partners, this is indicated by an increase in discipline in carrying out congregational prayer. Mitra (fifth-grade students at Al-Hikma Elementary School) have been able to perform prayers independently and perform congregational prayers, namely the Dhuha prayer. Students' memorization of short surahs has increased with the increasing number of surahs memorized. Positive results were also seen in activities carried out at Al-Hikma Elementary School, where 83% (15 students) have been disciplined in performing congregational prayers, the number of short surahs memorized has increased, and they have been routinely performing the Dhuha prayer and the Yasin prayer on Fridays. The remaining 17% (3 students) have a fairly good understanding. The results of the practicum carried out by the students independently also indicate that they are able to perform ablution, perform prayers, and recite short surahs well.Keywords: Discipline; Congregational Prayer.